Trading Platform for the Global Warrant Markets - Iosif ZIMAN (Informatică economică, 2011)
Global warrant markets are among the most active financial markets in the retail derivatives investment landscape currently. In this context some of the most relevant markets in the last years have been the ones across Asia and in particular Hong Kong, Korea and Japan. This paper introduces the financial instruments used in connection with the warrant markets, pre-sents and offers suggestions for setting up a generic warrant market making system and in-troduces the main concepts and components that need to be taken into account when develop-ing these systems targeting an exchange driven or E-Businesscontext.